The end game – A quantitative assessment tool for anastomosis in simulated microsurgery. Issue 6 (June 2020) - Kim, Eunsol; Norman, Irena C.F.; Myers, Simon; Singh, Masha; Ghanem, Ali
Summary: With the move towards simulation based microsurgical training and emphasis on the declining usage of animal models, there is a need for an objective method to evaluate microvascular anastomosis in a non-living, simulated microsurgical training environment. Our aim was to create a validated assessment tool to evaluate the intimal surface of the end product to measure skills acquisition. The intimal surface of 200 anastomoses from 23 candidates and 2 experts were assessed using ImageJ to measure 4 parameters: 1) distance between the distal insertion points, 2) distance between the proximal insertion points, 3) length of sutures placed, 4) number of axes. Using these parameters, a 9-component scoring system was produced based on the hypothesis of the ideal anastomosis having equidistance between the above parameters. The scoring system was devised based on population performance to give a maximum score of 100. The EPIA tool demonstrated its ability to differentiate between seniority from undergraduate to expert. Furthermore, predictive validity was shown by demonstrating skill acquisition between day 3 and 5 of the microsurgery course. The EPIA tool is a valid and feasible method to assess and provide feedback regarding the end product as an adjunct to current scoring systems in simulated microsurgery.